Results of a phase II study of thalidomide and azacitidine in patients with clinically advanced myelodysplastic syndromes (MDS), chronic myelomonocytic leukemia (CMML) and low blast count acute myeloid leukemia (AML). Issue 2 (1st February 2017) - Kenealy, Melita; Patton, Nigel; Filshie, Robin; Nicol, Andrew; Ho, Shir-Jing; Hertzberg, Mark; Mills, Tony; Prosser, Ian; Link, Emma; Cowan, Linda; Zannino, Diana; Seymour, John F.
Abstract: Single agent azacitidine or immunomodulatory drugs are effective in myelodysplastic syndrome (MDS), with differing target mechanisms and toxicities. Objectives of this ALLG MDS3 study in clinically advanced MDS, AMML and low blast AML were to establish safety, response and quality of life of azacitidine and thalidomide. Patients received azacitidine (75mg/m 2 /d sc 7days every 28 days), and oral thalidomide up to 100mg/d for maximum 12months. Eighty patients registered; median age 68 years (range 42–82), 49% IPSS int2-high. With 36.5 months follow up, patients received median 9 cycles azacitidine, 6.1mths thalidomide. Nonhematologic toxicity grade 3+ in 85%, commonly infections. Overall response rate was 63%; 26% CR were unaffected by IPSS. Median response duration 26.3months; overall survival was 28.1months. This combination azacitidine and thalidomide in clinically advanced MDS, CMML and low-blast AML was tolerable without unexpected toxicity and encouraging responses support further investigation of combination approaches with hypomethylating agent and immunomodulatory drug.